The histological response to a xenogeneic tumour in mice. - Simpson, E; Beverley, P (1973)
The authors have examined, by conventional histological methods, the immune response of normal and antilymphocyte serum (ALS) treated mice to a tumour xenograft. In normal mice the histology of the tumour site and lymphoid organs is in agreement with the hypothesis that rejection of tumour is by a cell mediated response. In ALS treated mice, lymphoid organs severely depleted of small lymphocytes, show many blast cells which may be responsible for in vitro cytotoxicity. After cessation of ALS there is still a striking lack of infiltrate at the tumour site suggestive of some form of 'blocking' mechanism.